Tsukamurella catheter-related bloodstream infection in a pediatric patient with pulmonary hypertension - Kristen A. Wendorf; Claudia M. Espinosa; William D. LeBar; Jason B. Weinberg (MDPI AG, 2010)
Catheter-related bloodstream infections (CR-BSI) are important complications in patients with long-term indwelling central venous catheters. In this report, we present the case of a 14-year-old male with pulmonary hypertension treated with continuous treprostinil infusion, who presented with a CR-BSI caused by a Tsukamurella species. This case highlights the potential for this unusual organism to cause infection in immunocompetent patients.